2009
DOI: 10.1086/596500
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pneumococcal Disease in Children Aged <5 Years Admitted to 3 Urban Hospitals in Ibadan, Nigeria

Abstract: Of the pneumococcal serotypes identified, 55% were covered by the licensed 7-valent pneumococcal conjugate vaccine, whereas all are covered by the 10- and 13-valent vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 16 publications
7
57
1
Order By: Relevance
“…These data indicate the need for the development of immunization programs, especially in poor countries, to reduce morbidity and mortality (273). Surveillance studies of serotypes causing invasive pneumococcal disease in developing countries have also demonstrated that the current 7-valent pneumococcal vaccine would not cover all serotypes causing invasive disease and have suggested that wider coverage would be provided by the 10-valent or 13-valent pneumococcal conjugate vaccines (13,17,22,98,173,221,267,273,283,307,351,354). The introduction of these vaccines into these vulnerable populations is a crucial, but expensive, step to control this serious infection.…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
“…These data indicate the need for the development of immunization programs, especially in poor countries, to reduce morbidity and mortality (273). Surveillance studies of serotypes causing invasive pneumococcal disease in developing countries have also demonstrated that the current 7-valent pneumococcal vaccine would not cover all serotypes causing invasive disease and have suggested that wider coverage would be provided by the 10-valent or 13-valent pneumococcal conjugate vaccines (13,17,22,98,173,221,267,273,283,307,351,354). The introduction of these vaccines into these vulnerable populations is a crucial, but expensive, step to control this serious infection.…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
“…These serotypes are therefore part of the minimally acceptable target product profile for pneumococcal conjugate vaccines (PCVs) for African countries that are eligible for support from the Global Alliance for Vaccines and Immunization (GAVI) 3 . Nigeria qualifies for GAVI support 4 but PCV immunization is not yet used widely in this country and there are limited data on pneumococcal serotype distribution among young Nigerian children with pneumococcal disease 5 , 6 . A recent analysis of children aged under 5 y with pneumococcal meningitis conducted in 8 West African countries including Nigeria found pneumococcal serotypes 1 and 5 were most common, accounting for approximately half of all pneumococcal isolates from cerebrospinal fluid samples 6 .…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Similar rates of S. pneumoniae bacteremia were described in other resource-poor settings like Nepal (1%) and Nigeria (2.2%). 19,20 The higher RT-PCR method sensitivity compared with blood culture may explain these differences. The work by Resti and others 21 compared the performance of blood cultures and real-time PCR for the detection of S. pneumoniae bacteremia among children admitted with pneumonia to 83 Italian hospitals.…”
Section: Discussionmentioning
confidence: 99%